The rise of professional society : England since 1880 - Perkin, Harold James (Routledge, 2002)
A stimulating and controversial framework for the study of British society, challenging accepted paradigms based on class analysis. Perkins argues that the non-capitalist "professional class" represents a new principle of social organization